2014
DOI: 10.1163/15685403-00003288
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Patagonian planktonic copepods to fluctuations in temperature and UV radiation

Abstract: The aim of this investigation is to address the impact of fluctuations in temperature and ultraviolet radiation (UVR) on three species of South American copepods, Boeckella antiqua, B. gracilis and B. brevicaudata. These copepods are cold stenotherm and occur in high latitude lakes of South America and in mountain lakes in the Andes. The forecast scenarios for climate change in southern South America anticipate raising temperature and UVR levels. These changes may have the potential to impact high altitude and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Six of the 14 species of Boeckella occurring at high latitudes recorded in this study have been reported as exclusively distributed south of 40°S in South America ( B.brevicaudata , B.vallentini , B.silvestrii , B.antiqua Menu-Marque & Balseiro 2000, B.michaelseni and B.longicauda Daday 1901). In particular, B.silvestrii , reported from 44° to 50°S on the Argentine Patagonian Plateau (Menu-Marque et al 2000), and B.antiqua , which has never been recorded in any location since its original description from an ephemeral pond in Argentine grassland (Menu-Marque and Balseiro 2000; Pérez et al 2012; Garcia and Dieguez 2014). In contrast, other species showed much wider distributions, in particular B.poppei which has been reported across the three Antarctic biogeographical zones (sub-Antarctic islands, maritime and continental Antarctic), as well as in southern South America.…”
Section: Discussionmentioning
confidence: 99%
“…Six of the 14 species of Boeckella occurring at high latitudes recorded in this study have been reported as exclusively distributed south of 40°S in South America ( B.brevicaudata , B.vallentini , B.silvestrii , B.antiqua Menu-Marque & Balseiro 2000, B.michaelseni and B.longicauda Daday 1901). In particular, B.silvestrii , reported from 44° to 50°S on the Argentine Patagonian Plateau (Menu-Marque et al 2000), and B.antiqua , which has never been recorded in any location since its original description from an ephemeral pond in Argentine grassland (Menu-Marque and Balseiro 2000; Pérez et al 2012; Garcia and Dieguez 2014). In contrast, other species showed much wider distributions, in particular B.poppei which has been reported across the three Antarctic biogeographical zones (sub-Antarctic islands, maritime and continental Antarctic), as well as in southern South America.…”
Section: Discussionmentioning
confidence: 99%
“…Annual rainfall in the area is 800 to 1400 mm, which largely determines the water regime of the pond. The hydroperiod of the pond generally lasts 8 to 9 mo (May to December), with maximum water levels registered in late autumn and winter and a maximum depth of 2 m. Water temperature ranges from 4°C in July and August (winter) to 20°C in December (Vega 1999, Garcia 2010.…”
Section: Study Systemmentioning
confidence: 99%
“…The zooplankton assemblage is dominated by 3 endemic centropagid calanoid copepods: 2 genera of Boeckella (B. brevicaudata and B. gracilis) and Parabroteas sarsi, which develops exclusively from dormant eggs to adulthood (Dieguez & Balseiro 1998, Vega 1999. B. brevicaudata is present during the first half of the hydroperiod, coexisting briefly with adults of P. sarsi, whereas B. gracilis appears during the second half of the hydroperiod, coexisting with adults of P. sarsi throughout its life cycle (Garcia 2010). The cyclopoid copepods Acanthocyclops robustus and Tropocyclops prasinus meridionalis are also present in the pond but in low densities.…”
Section: Study Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, temperature also affects physiology parameters such as metabolism level and oxygen consumption that, in turn, affect copepod's ability to resist environmental changes (Huntley & Lopez, 1992). High temperatures can accelerate metabolism and oxygen consumption, leading to excessive use of protein and a low survival rate (Li et al, 2009;Garcia & Diéguez, 2014). It is possible that a combination of these factors imposes severe restraints on P. sarsi females from spring onwards, differentially affecting their survival (Garcia et al, 2018).…”
mentioning
confidence: 99%